REGENERATION OF Pimpinella pruatjan THROUGH SOMATIC EMBRYOGENESIS - I. Roostika; R. Purnamaningsih; I. Darwati; I. Mariska (Indonesian Agency for Agricultural Research and Development, 2007)
Pruatjan (Pimpinella pruatjan Molk.) is an Indonesian endangered plant which has various medicinal properties such as aphrodisiac, diuretic, and tonic. The plant is commonly harvested from its natural habitat, therefore it becomes endangered. Regeneration of pruatjan through organogenesis has been studied, but its shoot multiplication was very low (5 shoots per explant). The study aimed to investigate the best regeneration technique of pruatjan through somatic embryogenesis. This research was conducted at the tissue culture laboratory, Indonesian Center for Agricultural Biotechnology and Genetic Resources Research and Development in 2004-2005. Callus formation of pruatjan was induced from the petioles and leaves in Driver and Kuniyaki’s (DKW) based medium containing 2,4-D combined with picloram at the level of 0.5, 1.0, 1.5, and 1.5 ppm. Embryogenic calli were then transferred into embryo development medium in two ways. First, they were directly transferred into media containing IBA/NAA at the level of 0.5, 1.0, and 1.5 ppm. Second, they were indirectly transferred into media containing 2.0 ppm 2,4-D and 0.3% casein hydrolysate prior to the IBA/ NAA media. Parameters evaluated were fresh weight, dry weight, time initiation of embryogenic callus formation, and total number of embryos. The result showed that calli of pruatjan were successfully induced from the petioles and leaves. The best calli were induced from the leaves in the DKW medium containing 2.0 ppm 2,4-D and 0.5 ppm picloram. Embryo development of the calli was best if they were first grown in the media containing 2.0 ppm 2,4-D and 0.3% casein hydrolysate then transferred to the IBA/NAA media. The total number of somatic embryos was counted up to 103 on the medium containing 1.5 ppm IBA. This study indicated that pruatjan somatic embryogenesis regeneration required three different media, i.e. for callus induction, development and maturation, and for germination.